Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! Let's find the limit as \( x \) approaches 1 for the expression \(\frac{x^7 - 1}{x^{20} - 1}\):
[tex]\[ \lim_{x \to 1} \frac{x^7 - 1}{x^{20} - 1} \][/tex]
We'll work through this step-by-step.
### Step 1: Recognize Indeterminate Form
When we substitute \( x = 1 \) directly into the expression, both the numerator and denominator become zero:
[tex]\[ x^7 - 1 = 1^7 - 1 = 0 \][/tex]
[tex]\[ x^{20} - 1 = 1^{20} - 1 = 0 \][/tex]
Hence, we have a \(\frac{0}{0}\) indeterminate form, and we need to apply a method to resolve this.
### Step 2: Apply L'Hôpital's Rule
L'Hôpital's Rule states that if we have a \(\frac{0}{0}\) indeterminate form, we can take the derivatives of the numerator and the denominator:
[tex]\[ \lim_{x \to 1} \frac{f(x)}{g(x)} = \lim_{x \to 1} \frac{f'(x)}{g'(x)} \][/tex]
In this case:
[tex]\[ f(x) = x^7 - 1 \][/tex]
[tex]\[ g(x) = x^{20} - 1 \][/tex]
We'll differentiate both functions with respect to \( x \):
[tex]\[ f'(x) = \frac{d}{dx}(x^7 - 1) = 7x^6 \][/tex]
[tex]\[ g'(x) = \frac{d}{dx}(x^{20} - 1) = 20x^{19} \][/tex]
### Step 3: Substitute the Derivatives
Now we substitute the derivatives back into the limit:
[tex]\[ \lim_{x \to 1} \frac{7x^6}{20x^{19}} \][/tex]
### Step 4: Simplify the Expression
We can simplify this new expression:
[tex]\[ \lim_{x \to 1} \frac{7x^6}{20x^{19}} = \lim_{x \to 1} \frac{7}{20} x^{6-19} = \lim_{x \to 1} \frac{7}{20} x^{-13} \][/tex]
### Step 5: Evaluate the Limit
Now, we evaluate the limit as \( x \) approaches 1:
[tex]\[ \frac{7}{20} \cdot 1^{-13} = \frac{7}{20} \][/tex]
(Note that \( 1^{-13} = 1 \))
### Conclusion
So the limit is:
[tex]\[ \lim_{x \to 1} \frac{x^7 - 1}{x^{20} - 1} = \frac{7}{20} \][/tex]
And that's our final answer.
[tex]\[ \lim_{x \to 1} \frac{x^7 - 1}{x^{20} - 1} \][/tex]
We'll work through this step-by-step.
### Step 1: Recognize Indeterminate Form
When we substitute \( x = 1 \) directly into the expression, both the numerator and denominator become zero:
[tex]\[ x^7 - 1 = 1^7 - 1 = 0 \][/tex]
[tex]\[ x^{20} - 1 = 1^{20} - 1 = 0 \][/tex]
Hence, we have a \(\frac{0}{0}\) indeterminate form, and we need to apply a method to resolve this.
### Step 2: Apply L'Hôpital's Rule
L'Hôpital's Rule states that if we have a \(\frac{0}{0}\) indeterminate form, we can take the derivatives of the numerator and the denominator:
[tex]\[ \lim_{x \to 1} \frac{f(x)}{g(x)} = \lim_{x \to 1} \frac{f'(x)}{g'(x)} \][/tex]
In this case:
[tex]\[ f(x) = x^7 - 1 \][/tex]
[tex]\[ g(x) = x^{20} - 1 \][/tex]
We'll differentiate both functions with respect to \( x \):
[tex]\[ f'(x) = \frac{d}{dx}(x^7 - 1) = 7x^6 \][/tex]
[tex]\[ g'(x) = \frac{d}{dx}(x^{20} - 1) = 20x^{19} \][/tex]
### Step 3: Substitute the Derivatives
Now we substitute the derivatives back into the limit:
[tex]\[ \lim_{x \to 1} \frac{7x^6}{20x^{19}} \][/tex]
### Step 4: Simplify the Expression
We can simplify this new expression:
[tex]\[ \lim_{x \to 1} \frac{7x^6}{20x^{19}} = \lim_{x \to 1} \frac{7}{20} x^{6-19} = \lim_{x \to 1} \frac{7}{20} x^{-13} \][/tex]
### Step 5: Evaluate the Limit
Now, we evaluate the limit as \( x \) approaches 1:
[tex]\[ \frac{7}{20} \cdot 1^{-13} = \frac{7}{20} \][/tex]
(Note that \( 1^{-13} = 1 \))
### Conclusion
So the limit is:
[tex]\[ \lim_{x \to 1} \frac{x^7 - 1}{x^{20} - 1} = \frac{7}{20} \][/tex]
And that's our final answer.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.